2010
DOI: 10.1016/j.healthplace.2010.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Social disparities in health: Disproportionate toxicity proximity in minority communities over a decade

Abstract: This study employs latent trajectory models measuring the level of toxic waste over a decade in the cities of six highly populated, ethnically diverse, counties in southern California from 1990-2000 in 3,001 tracts. We find that tracts with 15% more Latinos are exposed to 84.3% more toxic waste than an average tract over this time period and tracts with 15% more Asians are exposed to 33.7% more toxic waste. Conversely, tracts with one standard deviation more residents with at least a bachelor's degree (15.5%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 42 publications
(81 reference statements)
1
35
0
2
Order By: Relevance
“…Morello-Frosch and Jesdale used similar data to study residential segregation and estimated cancer risks associated with HAPs exposure in U.S. metropolitan areas and found that AAPIs as a group had higher estimated cancer risk than Non-Hispanic whites or blacks (61). Although few studies have evaluated potential disparities for the smaller and more diverse disaggregated AAPI groups, there has been a slowly growing body of literature suggesting that several of these groups face excess exposures to environmental hazards (28,(62)(63)(64) similar to other minority populations. Although our study is only exploratory in nature, the differences in estimated ambient air concentrations across and within the AAPI groups warrant further examination to identify potential disparities in environmental exposure by race and sociodemographics, which may inform future research directions in environmental-related adverse health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morello-Frosch and Jesdale used similar data to study residential segregation and estimated cancer risks associated with HAPs exposure in U.S. metropolitan areas and found that AAPIs as a group had higher estimated cancer risk than Non-Hispanic whites or blacks (61). Although few studies have evaluated potential disparities for the smaller and more diverse disaggregated AAPI groups, there has been a slowly growing body of literature suggesting that several of these groups face excess exposures to environmental hazards (28,(62)(63)(64) similar to other minority populations. Although our study is only exploratory in nature, the differences in estimated ambient air concentrations across and within the AAPI groups warrant further examination to identify potential disparities in environmental exposure by race and sociodemographics, which may inform future research directions in environmental-related adverse health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, there has been increasing evidence that minority and low-income populations have a disproportionate burden of exposures owing to residential proximity to areas with higher levels of pollutants, including air pollution (28)(29)(30)(31)(32). These observations suggest a need to examine environmental exposures, particularly air pollution, for the AAPI population, taking into consideration heterogeneity in ethnic and other sociodemographic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Early work highlighted the polluting wastes of manufacturing industries and their effects on environmental health, as well as controversies over waste management 20 infrastructures, where anti-incineration campaigns have been a backbone of studies linked to NIMBYism and locally unwanted land uses (LULUs) [120]. These concerns continue in the current literature [121,122,123,124]. …”
Section: Critiquementioning
confidence: 99%
“…Sicotte (2010) assigned hazard points to Philadelphia facilities and found that hazard burdens tended to be concentrated in areas with more minority residents, more vacant housing units, and more adults without a high-school diploma. Hipp and Lakon (2010) found that in six Southern California (USA) census tracts, those with more Latinos and Asians were more likely to be exposed to toxic waste, while those with a high proportion of residents with post-secondary education were less likely to be exposed. The effects were stronger when weights were applied to account for toxicity of the waste.…”
Section: Introductionmentioning
confidence: 99%